2014
DOI: 10.1007/s00442-014-3050-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shade tolerance and development stage on the allometry of ten temperate tree species

Abstract: Allometry studies the change in scale between two dimensions of an organism. The metabolic theory of ecology predicts invariant allometric scaling exponents, while empirical studies evidenced inter- and intra-specific variations. This work aimed at identifying the sources of variations of the allometric exponents at both inter- and intra-specific levels using stem analysis from 9,363 trees for ten Eastern Canada species with a large shade-tolerance gradient. Specifically, the yearly allometric exponents, α(v,D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 50 publications
(72 reference statements)
0
17
0
Order By: Relevance
“…Our models predict diameter growth as a function of stem diameter, and because of the nonlinear relationship between stem diameter and biomass, an asymptotic power law relationship between biomass and biomass growth will result in a unimodal and approximately lognormal shape to the relationship between diameter and diameter growth for at least some values of the power law exponent. But the broad range of shapes of the estimated relationships between stem diameter and diameter growth for the 50 species analyzed here (Appendix ) suggests that there indeed is a broad range of ontogenetic size relationships possible among tree species (Franceschini and Schneider , Iida et al. ).…”
Section: Discussionmentioning
confidence: 86%
“…Our models predict diameter growth as a function of stem diameter, and because of the nonlinear relationship between stem diameter and biomass, an asymptotic power law relationship between biomass and biomass growth will result in a unimodal and approximately lognormal shape to the relationship between diameter and diameter growth for at least some values of the power law exponent. But the broad range of shapes of the estimated relationships between stem diameter and diameter growth for the 50 species analyzed here (Appendix ) suggests that there indeed is a broad range of ontogenetic size relationships possible among tree species (Franceschini and Schneider , Iida et al. ).…”
Section: Discussionmentioning
confidence: 86%
“…Experimental studies on seed germination together with studies on seedling, juvenile and adult plants reveal important temporal changes in the traits conferring shade tolerance, in the dimensions of the ecological niche and in the nature and strength of plant-plant interactions during the lifetime of a plant (Miriti 2006;Quero et al 2008). Recent studies have shown that the influence of shade tolerance on biomass allocation can differ in juvenile and adult trees of the same species (Franceschini and Schneider 2014;Grubb 2015) Light partitioning, species coexistence and the niche There is a consensus that shade tolerance is at the heart of many ecological processes scaling from populations to ecosystems (Smith and Huston 1989;Zavala et al 2007;Laanisto and Niinemets 2015). In particular, interspecific differences in the ability to compete for light and in shade tolerance are considered key determinants of forest stand structure and dynamics.…”
Section: Ontogenetic Effects: Shade Tolerance From Seedlings To Adultsmentioning
confidence: 99%
“…Possible lidar data underestimation of tree height due the 5 years growth discrepancy between lidar data collection (2003) and field measurements was considered minimal. Analysed forests were at the mature stage (20-30 years old) therefore minimal growth was assumed (Brassard et al 2009;Franceschini and Schneider 2014). Trees with diameters smaller than 5 cm were excluded.…”
Section: Field Measurementsmentioning
confidence: 99%